La cultura visual desde el campo social de la mirada - Marquina, Orietta (2016)
It continues a theoretical reflection started with her master degree thesis about visuality as a feature of contemporary culture. It tries to explain what is meant by visual culture from the analysis of the social field of “seeing”. First, it presents the concept to, then, develop three analysis perspectives: the “seeing” that builds meaning, the “seeing” that sees the Other, and the “seeing” with which the subject sees himself. Visual culture organizes the daily action of the subject and creates meaning. The visual has been gaining space in the daily life of people. It has move from a marginal place, reserved for rituals and special performances, to fulfill a key role today that relates to identity and the way people learns. Everyday life has taken a visual twist that makes the “seeing” and life itself, practices qualitatively different to how they used to be before.